A personal reflection on health: 20 years on. (January 2016) - Radley, Alan
This article looks back to the origins of health : from the perspective of its Founding Editor. Reviewing the journal's original statement of aims, the terms 'refraction' and 'moment' are selected to provide a brief discussion of health and illness as defining the journal's continuing focus.